Дослідження ранньоскіфського кургану біля с. Купин на Хмельниччині - Гуцал, В.А. (Археологія і давня історія України, 2019)
У статті йдеться про результати досліджень курганів VII ст. до н. е. в с. Купин Городоцького р-ну
Хмельницької обл., які кілька років тому пограбували. В одному із насипів була споруджена і згодом
спалена дерев'яна усипальниця. Виявлено залишки двох захоронень, багатий набір керамічних виробів,
залізні сокири, два тесла, долото і дві намистинипронизки. In 2018 the archaeological expedition of Kamianets-
Podilskyi Ivan Ohiienko National University investigated
a group of four mounds of the Early Scythian
time in v. Kupyn, Gorodok district of Khmelnitskyi
region. All of them are seriously robbed at different
times. The work was carried out on two mounds.
Mound 3 with a diameter of 15 m, height up to 1 m,
damaged by predatory pits. There was built wooden
tomb, which later burned. A powerful flame enveloped
the whole space and burned the soil to a bright brick
color. At one of the sites that were touched by the robbers, the remains of two graves were discovered at the
level of the ancient surface. The burial site was filled with yellow clay over an area of 1.1 × 0.45 m. The first
burial was the remains of a single body, which was in a crouched condition. When the wooden structures
of the mound were burning, the skeleton also burned down. Preserved fragments of one leg, femur and tibia,
knee joint, several fragments of pelvic bones. The second burial was located next to the first one, but a
little south-east. Here, calcified bones were piled up 19 earthen vessels were broken at the buried. Among
them are two bank pots, a large and a small claypots, two bowls with a curved edge, two other bowls have a
crown bent outward. The whole series presents scoops with a low cup and a high handle with a performance.
One of the scoops is made on a potter’s wheel. With tools found, made of iron ax, two ax-tesla, chisel.